Mitochondrial Transplantation Moderately Ameliorates Retinal Degeneration in Royal College of Surgeons Rats - Shih-Fang Wu; Chih-Yao Lin; Rong-Kung Tsai; Yao-Tseng Wen; Feng-Huei Lin; Chia-Yu Chang; Ching-I Shen; Shinn-Zong Lin; Horng-Jyh Harn; Tzyy-Wen Chiou; Chin-San Liu; Yan-Ting Chen; et al. (Biomedicines, 2022)
Retinal pigmented epithelial (RPE) cells possess high mitochondria content for energy production, which is required for phagocytosis and vision cycle metabolism. The mitochondrial integrity in RPE cells helps the homeostasis of photoreceptor turnover and prevents retina aging and degeneration. Mitochondrial transplantation benefits the recovery of several acute inflammatory diseases, leading us to investigate the effects of mitochondrial transplantation on retina degeneration. Allogeneic mitochondria were isolated and delivered into the vitreous chamber in the Royal College of Surgeons (RCS) rats, which exhibit inherited and early-onset retina degeneration. The progress of retina degeneration was examined with optical coherence tomography (OCT) and visual evoked potential (VEP) to determine the retina thickness and integrity of afferent electrical signals from affected eyes, respectively. We found that mitochondria engraftment moderately attenuated the degeneration of retinal layers in RCS rats by histological examination. This result was consistent with the OCT measurement of retina thickness around the optic disc. The VEP analysis revealed that the peak one (N1) latency, representing the arriving time of electrical impulse from the retina to cortex, was substantially maintained as the normal value after the mitochondrial transplantation. This result suggests that the intra-vitreous transplanted mitochondria ameliorate the degeneration of photoreceptors in RCS rats and might be potential for clinical application.